Pembuatan Patty Vegan Berbahan Dasar Tempe dan Sayuran dengan Penambahan Isolat Soy Protein (ISP) - Shafiyyatul Rahil; Any Sutiadiningsih; Sri Handajani; Niken Purwidiani (Lembaga Pengembangan Kinerja Dosen, 2024)
This study developed an innovative vegan patty product with a combination of vegetable protein, cauliflower, and soy protein isolate with 3 different proportions: 25g, 35g, and 45g. Organoleptic tests are performed to evaluate the outer color, inner color, shape, aroma, taste, and texture. This study aims to determine the effect of the addition of soy protein isolate on the results so vegan patty made from tempeh and vegetables, comparing the content of making vegan patty with the nutritional content of the best products soy protein isolate and know the selling price of vegan patty made from tempeh and vegetables with the addition of soy protein isolate by using the method of food cost and cost plus pricing. The addition of 25g of isolate soy protein flour has the highest value and stands out with the characteristics of the outer color which is brown, the outer color which is light brown, the aroma of tempeh and vegetables is balanced, the texture is chewy, the savory taste of tempeh and vegetables is balanced, the round shape is quite perfect, from all assessment criteria the best results in the criteria for evaluating liking are in the addition of 25g of isolate soy protein flour. Laboratory analysis of the nutritional content of the best vegan patty which has an energy content of 179.60kcal/100gram, protein content of 14.52%, carbohydrate content of 21.90%, fat content of 2.54%, and fiber content of 4.81%. The selling price of vegan patty products with the addition of soy protein isolate obtained a result of Rp 4,891 / 55 g.